Characteristics and outcomes of pediatric open globe injury - Janejit Choovuthayakorn (2018)
To describe the epidemiology, mechanism of injury, and final visual and anatomical outcomes of pediatric patients with open globe injury. The medical records of patients aged ≤16 years diagnosed with open globe injury between January 2006 and December 2010 were retrospectively reviewed. Forty-nine pediatric patients were diagnosed with open globe injury during the study period. Forty-one of the 49 patients (83.7 %) were male. The mean age of the patients was 9.3 ± 4.6 years, with 49 % of the injuries occurring in patients between the ages of 11 and 16 years. Ocular penetration was the most common type of injury (63.3 %), occurring most frequently in the cornea (63.3 %). Wooden objects were the most common cause of injury. Following surgical intervention, 40.8 % of the patients obtained a final visual acuity (VA) of ≥6/60. Pars plana vitrectomy was performed in 51 % of cases, with only 36 % of these patients having a final VA of ≥6/60. The presence of retinal detachment was the only statistically significant factor (odds ratio 0.05, p < 0.001) that affected VA improvement of more than one line. Corneal penetration was frequently observed in pediatric patients with ocular trauma. Pediatric patients with a retinal detachment were significantly more likely to have a poor final visual outcome than open globe patients whose retina remained attached. Despite prompt surgical intervention, useful vision was preserved in less than half of the patients requiring pars plana vitrectomy. © 2013 Springer Science+Business Media.